PENGARUH PENAMBAHAN UNSUR Cr DAN Cu TERHADAP KEKUATAN TARIK BESI COR KELABU FC20 - Suprihanto, Agus; Satrijo, Djoeli; Suratman, Rochim (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2007)
The mechanical properties of grey cast iron are influenced by cooling rate, thickness of casting, heat treatment,liquid treatment and alloying. Some aplications of its materials need high strength grey cast iron. To improve itstensile strength usually its added with unsures which known as carbide promoteur ie. Cr and Cu.In these research the effect of Cr and Cu on the mechanicals properties of grey cast irons has been evaluated.Base material FC 20 which alloyed with Cr 0,23 %, 0, 32% and 0,47% and Cu between 0,6% to 0,7% have beentested. The tensile test and metallographyc examinations have been conducted to known of its efects.From tensile test there is an improvement of tensile strength about 20% from 191MPa to 232MPa. However themicrostructure of specimens are same which are pearlitic grey cast irons, with graphite type VII (flake), Adistributions and size of graphite are 3-5.